(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Endometrial cancer in women over 50 years of age is more aggressive in terms of the histological type of tumor, the degree of its differentiation, and the stage of the disease, characterized by an unfavorable prognosis.